2021
DOI: 10.1021/acsestwater.0c00141
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Really Clean Water: Combining Nanofiltration with Granular Activated Carbon and Anion Exchange Resins for the Removal of Per- And Polyfluoralkyl Substances (PFASs) in Drinking Water Production

Abstract: The removal of per-and polyfluoroalkyl substances (PFASs) presents a challenge for drinking water providers. Guidelines for PFAS concentrations in final drinking water are regularly updated to ever-decreasing values, and conventional drinking water treatment plants are not designed to remove PFASs. Currently, the most frequently used removal technique, adsorption to granular activated carbon (GAC), is often considered challenging. High-pressure membranes, such as nanofiltration (NF), have been shown to remove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 48 publications
6
52
1
Order By: Relevance
“…Proven methods for PFAS removal include adsorption via granular active carbon (GAC), powdered activated carbon (PAC), and anion exchange (AIX) or via size exclusion using reverse osmosis (RO) or nanofiltration (NF) (Appleman et al, 2013; Appleman et al, 2014; Belkouteb et al, 2020; Crone et al, 2019; Du et al, 2014; Franke et al, 2019; Franke et al, 2021; Kucharzyk et al, 2017; McNamara et al, 2018; Ochoa‐Herrera & Sierra‐Alvarez, 2008; Rahman et al, 2014; Senevirathna et al, 2010; Woodard et al, 2017; Zaggia et al, 2016; Zeng et al, 2020) and have been utilized in full‐scale predominantly for drinking water and groundwater treatment. For GAC and AIX adsorption processes, PFAS removal efficiency has been shown to be dependent on the PFAS chain length, functional group, pH, and is typically negatively affected by the presence of dissolved organic matter (DOC) (Dixit et al, 2019; Gagliano et al, 2020; Kothawala et al, 2017; McCleaf et al, 2017; Schuricht et al, 2017; Siriwardena et al, 2019) and other negatively charged ions.…”
Section: Introductionmentioning
confidence: 99%
“…Proven methods for PFAS removal include adsorption via granular active carbon (GAC), powdered activated carbon (PAC), and anion exchange (AIX) or via size exclusion using reverse osmosis (RO) or nanofiltration (NF) (Appleman et al, 2013; Appleman et al, 2014; Belkouteb et al, 2020; Crone et al, 2019; Du et al, 2014; Franke et al, 2019; Franke et al, 2021; Kucharzyk et al, 2017; McNamara et al, 2018; Ochoa‐Herrera & Sierra‐Alvarez, 2008; Rahman et al, 2014; Senevirathna et al, 2010; Woodard et al, 2017; Zaggia et al, 2016; Zeng et al, 2020) and have been utilized in full‐scale predominantly for drinking water and groundwater treatment. For GAC and AIX adsorption processes, PFAS removal efficiency has been shown to be dependent on the PFAS chain length, functional group, pH, and is typically negatively affected by the presence of dissolved organic matter (DOC) (Dixit et al, 2019; Gagliano et al, 2020; Kothawala et al, 2017; McCleaf et al, 2017; Schuricht et al, 2017; Siriwardena et al, 2019) and other negatively charged ions.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Also, the breakthrough of short-chain PFAS for GAC was reported to be rapid, making GAC a challenging technique for long-term PFAS remediation. 13 Membrane filtration, including nanofiltration and reverse osmosis, was also shown to effectively remove PFAS to levels greater that 90%. 14,15 The two filtration methods removed not only both long chains and short chains of PFAS but also other small molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Adsorption technologies, such as GAC, PAC, and AIX, are often coupled with membranes to separate PFAS (Franke et al, 2019, 2020; Murray et al, 2019). GAC and AIX show up to fourfold improved PFAS removal efficiency when applied to treat NF concentrate streams compared with GAC or AIX treatment of the raw water (Franke et al, 2019).…”
Section: Further Concentration Of Membrane Concentratesmentioning
confidence: 99%
“…GAC and AIX show up to fourfold improved PFAS removal efficiency when applied to treat NF concentrate streams compared with GAC or AIX treatment of the raw water (Franke et al, 2019). The cost of GAC and AIX treatment for NF concentrate depends on discharge volume and drinking water treatment goals in the drinking water treatment plant (Franke et al, 2020). Franke et al reported that AIX resins may be more cost‐effective than GAC to treat NF concentrate for many discharge goals.…”
Section: Further Concentration Of Membrane Concentratesmentioning
confidence: 99%